The Removal of the Judge as a Guarantee of Fair Criminal Justice - Yury V. Derishev; Vasiliy E. Krasnov (Сибирское юридическое обозрение, 2016)
The article is devoted to the institution of the removal of a judge in criminal trial proceedings, which is regarded as the most important guarantees of fair criminal justice. Based on the definition of the nature and content of the mechanism for the removal of a judge, the Authors offer an analysis of the problems of the application of law that accompany its implementation in modern criminal proceedings.